INTELLIGENT FAMILY MOVEMENT THROUGH FAMILY EMPOWERMENT IN THE KARYA BARU VILLAGE - Noor Amaliah (UMBanjarmasin, 2022)
Stunting is a condition in which an toddler has a leght and heights are less when compared with aged caused by multidimensional factors. One the factors related to incidence of stunting is nutritional factors, and community knowledge for stunting prevention. The purpose of this community service is to increase the knowledge of the people of Karya Baru Village about stunting prevention. This community services is carried out as a form the contribution of accelerating stunting reduction. The importance of community participation in stunting prevention and early detection programs. The method used is a measuring nutritional status, providing information through stunting education by installing posters and assisting in making nuggets. the reults of this services, in general, this activity provides an increase in community understanding and commitment to stunting and efforts to assist children’s growth and development.